IDENTIFIKASI JALUR PATAHAN DENGAN METODE GEOLISTRIK HAMBATAN JENIS DI WILAYAH PALU BARAT - Fitriani, Zelly Rizky; Rusydi H., Muhammad; Th Musa, Moh. Dahlan (Natural Science: Journal of Science and Technology, 2012)
Research identify fault lines with resistivity geoelectric measurements in West Palu has been done. This study aimed to determine the geological structure, and also the type of rock layers below  the  surface  area  of  research.  This  measurement  was  carried  out  in  two  areas  in  the western district of Palu, the Kalora and Kabonena, using geoelectric methods resistance type with Wenner configuration. Data processing was done using software EarthImager 2D. From the results of treatment, obtained a description of the geological structure in line 2 at Kalora areas there resistance values between 1212-6000 ohm-m which allegedly was granite layer that  separated  by  a  layer  of  sandy  loam  with  a  resistance  value  of  200-1000  ohm-m  in coordinates of 119 °49'33,7? BT and 00 ° 52'42, 5" LS, which was characteristic of the fault.